2018
DOI: 10.1136/annrheumdis-2018-213904
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low-dose CT detects synovitis in patients with suspected rheumatoid arthritis

Abstract: PurposeTo prove the feasibility and measure the diagnostic accuracy of contrast-enhanced ultra-low-dose CT (ULD-CT) for the depiction of inflammatory soft-tissue changes (synovitis, tenosynovitis and peritendonitis) in patients with arthritis of the hand.Materials and methodsIn this institutional review board–approved study, 36 consecutive patients over the age of 50 with suspected rheumatoid arthritis underwent ULD-CT (estimated radiation exposure <0.01  mSv) and MRI of the hand with weight-adapted intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…However, many studies used low dose for lower than standard or conventional CT dose (13,14). Furthermore, several studies used "ultra-low-dose" for lower than low-dose CT (10,15,16). In the present study, the dose results were the lowest in the literature.…”
Section: Introductionmentioning
confidence: 58%
“…However, many studies used low dose for lower than standard or conventional CT dose (13,14). Furthermore, several studies used "ultra-low-dose" for lower than low-dose CT (10,15,16). In the present study, the dose results were the lowest in the literature.…”
Section: Introductionmentioning
confidence: 58%
“…Additionally, CT is faster and more readily available. In our previous study, we showed that patients prefer CT than MRI and feel more comfortable in a CT scanner [ 13 ]. For comparability with MRI, CT examinations in our study were performed in the superman position as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography can be offered as an alternative imaging test [10], but the results are often dependent on the experience of the examiner and difficult to quantify [11]. The first studies investigated the capability of computed tomography (CT) in the detection of active inflammation [12,13]. Dynamic contrast-enhanced computed tomography (DCE-CT) has the potential to provide a differentiated estimation of inflammatory joint lesions through the assessment of perfusion parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Our study population constituted a convenience series and included patients, who were referred to the inpatient or outpatient clinic of rheumatology in our institution with suspected or known rheumatoid arthritis, the latter fulfilling the classification criteria of the American College of Rheumatology (ACR) 31. We analysed data from prospectively recruited patients during a previous study at our institution from September 2016 to October 2017 5 32. Diagnosis was established by board-certified rheumatologists by clinical findings (history, swollen and tender joints), laboratory findings (C reactive protein, rheumatoid factors, anticitrullinated protein antibodies) and imaging findings.…”
Section: Methodsmentioning
confidence: 99%
“…No exclusion criteria applied other than age >50 years (due to a requirement of our local ethics committee) and absent contraindications to the MRI procedure. Patients were involved by systematically surveying their concerns and comfort with the MRI examination as previously detailed 5 32…”
Section: Methodsmentioning
confidence: 99%